THE EFFECT OF KNOWLEDGE MANAGEMENT IMPLEMENTATION ON EMPLOYEE PERFORMANCE - Prayogo, Dehan Kukuh; Lestari, Rini (UPT Publikasi Ilmiah UNISBA, 2024)
Abstract In a company, it is very necessary to monitor and improve the performance of its employees. Employee performance is important for the company because with good performance, employees can contribute to the company's success in achieving the company's vision and mission. The variable that can affect employee performance is knowledge management. The purpose of this study is to explain whether or not knowledge management affects employee performance at PT Berlio Anugrah Putra. This research method uses a quantitative survey method. The data source used was obtained from employees of PT Berlio Anugrah Putra. In addition, the sampling technique in this study used non-probability sampling with convenience sampling technique. The population in this study consisted of all employees of PT Berlio Anugrah Putra with approximately 500 employees, so a sample of 89 respondents was obtained. The analytical tool used in this research is SmartPLS version 3.2.9. The results of this study indicate that knowledge management affects employee performance. Keywords: Knowledge Management, Employee Performance, Company Success